Application of Human Placental Blood Serum as Perspective Method to Correct Atherosclerotic Changes (Experimental Study) - Falko, O. V. (Problems of Cryobiology and Cryomedicine, 2012)
There was demonstrated the possibility to correct the lipid metabolism disorders and to recover an aortic structure in rabbits with experimental atherosclerosis by administration of human placental blood serum (HPBS). The HPBS application has been established to increase the level of antiatherogenic fraction of lipoproteins in blood, to reduce the rate of aortic lipoidosis, as well as to recover the integrity of endothelial layer.